Dari Konformitas Ke Normalisasi: Analisis Sosiologi Kriminal Terhadap Pelecehan Mahasiswi Di Lingkungan Perguruan Tinggi - Risandi; Syalia Sefitriani; Andy Suhendra; Hayati Pelita; Soni; Endri Bagus Prastyo (Universitas Halu Oleo (UHO), 2026)
This research aims to analyze how group conformity develops into a form of normalization of verbal sexual display behavior in higher education environments in Indonesia through the perspective of Criminal Sociology. This research uses a qualitative descriptive method with an analytical literature study approach through academic literature, relevant regulations, as well as cases that became public attention in April 2026, namely the case of the student conversation group at the Faculty of Law, University of Indonesia and the controversy over the song